Whatever Happened to Gramsci? Some Reflections on New Legal Realism. (30th July 2015) - KLABBERS, JAN
Abstract: This article responds to five pieces published in the previous issue of the Leiden Journal of International Law, extolling the virtues of a new legal realism. I first express some doubts as to whether an awful lot can and should be expected from yet another new approach to the study of international law; earlier approaches widely heralded have quietly disappeared from sight, sometimes without leaving much trace. Subsequently, I discuss the extent to which the new international legal realism conceptualizes its notion of empirical reality, followed by a discussion on which interests the new insights spawned by new legal realism are to serve.